Factors influencing students’ motivation towards learning - NorHasnida Che Md Ghazali; Zahari Suppian; Syaza Hazwani Zaini; SitiFazlyana Mat Husin (Jurnal Cakrawala Pendidikan, 2022)
Students’ motivation towards learning comes from inside of themselves, which seems to be an important factor in determining success. The material and personal needs (input dimension), the teachers’ knowledge and attitude, and challenges faced by the teachers regarding school-based assessment (the process dimension) are considered to influence students’ motivation towards learning. This study was conducted to explore the degree of influence of factors regarding school-based assessment implementation on students’ motivation towards learning. There were 879 teachers selected using a stratified sampling method. The instrument was developed by the researcher following the CIPP evaluation model by Daniel Stufflebeam. The analysis used a two-step approach involving measurement and structural model using structural equation modeling (SEM) analysis. Results of the study indicated that the proposed model was supported. Five inter-correlated constructs had good psychometric properties. Out of four constructs, two constructs loaded positively on motivation towards learning. In conclusion, good teachers will engage in improving their knowledge and skills and combat the challenges and hence, improving their practices to continually improve their students’ performance. The findings will give rise to further hypotheses